Genome-wide identification, interaction of the MADS-box proteins in Zanthoxylum armatum and functional characterization of ZaMADS80 in floral development - Tang, Ning; Cao, Zhengyan; Wu, Peiyin; Zhang, Xian; Lou, Juan; Liu, Yanni; Wang, Qiyao; Hu, Yang; Si, Shuo; Sun, Xiaofan; Chen, Zexiong (Frontiers in Plant Science, 2022)
As a typical dioecious species, Zanthoxylum armatum establishes apomictic reproduction, hence only female trees are cultivated. However, male and hermaphrodite flowers have recently appeared in female plants, resulting in a dramatic yield reduction. To date, the genetic basis underlying sex determination and apomixis in Z. armatum has been largely unknown. Here, we observed abortion of the stamen or carpel prior to primordium initiation, thus corroborating the potential regulation of MADS-box in sex determination. In Z. armatum, a total of 105 MADS-box genes were identified, harboring 86 MIKC-type MADSs with lack of FLC orthologues. Transcriptome analysis revealed candidate MADSs involved in floral organ identity, including ten male-biased MADSs, represented by ZaMADS92/81/75(AP3/PI-like), and twenty-six female-specified, represented by ZaMADS80/49 (STK/AGL11-like) and ZaMADS42 (AG-like). Overexpressing ZaMADS92 resulted in earlier flowering, while ZaMADS80 overexpression triggered precocious fruit set and parthenocarpy as well as dramatic modifications in floral organs. To characterize their regulatory mechanisms, a comprehensive protein-protein interaction network of the represented MADSs was constructed based on yeast two-hybrid and bimolecular fluorescence complementation assays. Compared with model plants, the protein interaction patterns in Z. armatum exhibited both conservation and divergence. ZaMADS70 (SEP3-like) interacted with ZaMADS42 and ZaMADS48 (AP3-like) but not ZaMADS40 (AP1-like), facilitating the loss of petals in Z. armatum. The ZaMADS92/ZaMADS40 heterodimer could be responsible for accelerating flowering in ZaMADS92-OX lines. Moreover, the interactions between ZaMADS80 and ZaMADS67(AGL32-like) might contribute to apomixis. This work provides new insight into the molecular mechanisms of MADS-boxes in sex organ identity in Z. armatum.